P141. Neuralgic amyotrophy associated with Hepatitis E infection – A case report. Issue 8 (August 2015) - Lang, K.; Weiler, M.; Wick, W.; Schnitzler, P.; Christoph, E.; Seker, F.; Bendszus, M.; Rizos, T.
<x xml:space="preserve">Abstract</x> Introduction The cause of neuralgic amyotrophy (NA; Parsonage–Turner syndrome) remains unknown, but different infections often precede NA, and an idiopathic autoimmune response generating nerve inflammation has been postulated. Hepatitis E virus (HEV) infections are endemic in developing countries (genotypes 1 & 2). Within the last years, an increasing number of locally acquired HEV infections have been described in western countries (genotypes 3& 4). We present here the case of a previously healthy 37 years old male with NA associated to autochthonous HEV infection, presumably caused by a meal of raw pork one week before symptom onset. Case report Admission was due to bilateral arm and upper spine pain with paraesthesia of both upper extremities. Previous orthopaedic presentation ruled out vertebral disk herniation, myelopathy and foraminal stenosis by Magnetic Resonance (MR) Imaging. Neurological examination revealed right-sided scapula alata and palsies of arm abduction, elbow flexion/extension, thumb opposition and finger splaying. Numbness was present on the radial side of both forearms. Right-sided biceps and triceps reflexes were reduced; Trömner's reflex was absent. Sensible and motoric nerve conduction velocity (NCV) of the median and radial nerve, F-wave examinations, sympathic skin reflex (SSR) and electromyography (EMG; anterior serratus and deltoid muscle) were normal. Liver enzymes were elevated: AST 325 U/L, ALT 1774 U/L, AP 304 U/L, GGT 205 U/L. Cerebral spinal fluid (CSF) revealed lymphomonocytic pleocytosis (14 cells/μl), signs of blood–brain–barrier disruption and elevated protein (77.6 mg/dl) with normal lactate and glucose levels. CSF HEV-, HSV-, VZV-PCR and Borellia IgM were negative. Further tests ruled out Treponema pallidum, Rubella, Rubeola, Mumps, TBE (tick borne encephalitis), Hepatitis A, B, C, HIV, CMV and EBV. Serum-HEV-RNA was positive (8.3 × 104 cop/ml; genotype 3c). Assuming HEV-associated NA, oral administration of methylprednisolone was started (80 mg, tapering thereafter), and patient's pain remarkably decreased. High resolution magnetic resonance neurography (3 Tesla) after two months revealed fascicular T2 hyperintense lesions of the ulnar, radial and median nerves and brachial and triceps muscle denervation. Clinical follow-up examination showed typical findings of a Parsonage–Turner syndrome with atrophy of the right upper arm muscles, (improved) scapula alata and palsies of elbow flexion, thumb opposition, flexion and finger splaying. Bilateral hypaesthesia on radial side of forearms persisted. Arm abduction and elbow extension improved. NCV, SSR and F-wave were again normal. However, EMG (abductor digiti minimi, flexor pollicis longus, flexor digitorum superficialis muscles) now discovered denervation. Conclusions NA is rare and association with Hepatitis E infections have been described in single patients. While diagnosis can be difficult, clinicians should consider this sporadic entity, particularly when typical neurologic signs are combined with elevated liver enzymes.